Outsourcing, offshoring and innovation: Evidence from firmlevel data for emerging economies - Ursula Fritsch; Holger Görg (Kiel Institute for the World Economy (IfW), 2013)
It is striking that by far the lion's share of empirical studies on the impact of outsourcing on firms considers industrialized countries. However, outsourcing by firms from emerging economies is far from negligible and growing. This paper investigates the link between outsourcing and innovation empirically using firm-level data for over 20 emerging market economies. We find robust evidence that outsourcing is associated with a greater probability to spend on research and development and to introduce new products and upgrade existing products. The effect of offshoring on R&D spending is significantly higher than the effect of domestic outsourcing. However, only domestic outsourcing increases the probability to introduce new products. We also show that the results crucially depend on the level of protection of intellectual property in the economy. Firms increase their own R&D effort in the wake of outsourcing only if they operate in an environment that intensively protects intellectual property.
Keywords: F14; O31; O34; 330; outsourcing; offshoring; innovation; emerging economies